2014
DOI: 10.1089/jwh.2014.4867
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Cognitive Behavioral Therapy for Pregnant Women with Major Depressive Disorder

Abstract: Background: Pregnant women with major depressive disorder (MDD) report that psychotherapy is a more acceptable treatment than pharmacotherapy. However, although results of several studies suggest that psychotherapy is an effective treatment for pregnant women, logistical barriers-including cost and traveling for weekly visits-can limit real-world utility. We hypothesized that computer-assisted cognitive behavior therapy (CCBT) would be both acceptable and would significantly decrease depressive symptoms in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…One identified record was a ‘letter to the editor’ [ 36 ]. The corresponding author was contacted and confirmed that the data within the letter were also included in a further publication identified in the literature search [ 37 ]. In addition, the corresponding author of three articles written by the same author [ 38 40 ] was contacted who confirmed that all three publications included data collected from one single study.…”
Section: Methodsmentioning
confidence: 99%
“…One identified record was a ‘letter to the editor’ [ 36 ]. The corresponding author was contacted and confirmed that the data within the letter were also included in a further publication identified in the literature search [ 37 ]. In addition, the corresponding author of three articles written by the same author [ 38 40 ] was contacted who confirmed that all three publications included data collected from one single study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of treatments concluded that in terms of pharmacotherapy, SSRIs and tricyclic antidepressants had some evidence for effectiveness in treating anxiety disorders in the perinatal period (150). For women who do not want to use medication during pregnancy, cognitive behavioral therapy (CBT) may be a good alternative, particularly for women with panic disorder or specific phobias (150; 151). …”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…This is accomplished by a low-intensity, nontherapeutic coaching role in the case of MumMoodBooster and more frequent calls by mental health workers trained in a “high-intensity perinatal-specific BA approach” in the case of Netmums. In the antenatal period, a recently pilot-tested computerized CBT intervention for depression among pregnant women has also shown significant improvements on self-report psychometric measures [ 33 ].…”
Section: Introductionmentioning
confidence: 99%